2018
DOI: 10.1002/ejhf.1358
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetes and sex in heart failure with reduced ejection fraction patients from the ASIAN‐HF registry

Abstract: Aims To examine sex differences in clinical characteristics, echocardiographic features, quality of life and 1‐year death or heart failure (HF) hospitalization outcomes in patients with/without diabetes mellitus (DM). Methods and results Utilizing the Asian Sudden Cardiac Death in HF (ASIAN‐HF) registry, 5255 patients (mean age 59.6 ± 13.1, 78% men) with symptomatic HF with reduced ejection fraction (HFrEF) were stratified by DM status to address the research aims. Despite similar prevalence of DM between Asia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 43 publications
5
55
0
Order By: Relevance
“…Asian patients have different characteristics compared with Western ones . Chandramouli et al . examined the interaction of sex and diabetes in 5255 patients enrolled in the Asian Sudden Cardiac Death in HF (ASIAN‐HF) registry.…”
Section: Epidemiologymentioning
confidence: 99%
“…Asian patients have different characteristics compared with Western ones . Chandramouli et al . examined the interaction of sex and diabetes in 5255 patients enrolled in the Asian Sudden Cardiac Death in HF (ASIAN‐HF) registry.…”
Section: Epidemiologymentioning
confidence: 99%
“…In this issue of the Journal, the paper by Chandramouli et al . addresses this issue and provides new insight into the relationship between diabetes mellitus (DM) and sex in HFrEF patients from the ASIAN‐HF registry.…”
mentioning
confidence: 99%
“…They found that Asian women with HFrEF were more likely to have DM and more concentric left ventricular geometry compared to men. Furthermore, DM confers worse quality of life and a greater risk of adverse outcomes in women than men . Among HF patients, DM is a common co‐morbidity and confers worse prognosis .…”
mentioning
confidence: 99%
See 2 more Smart Citations